KEKERASAN SEKSUAL TERHADAP PEREMPUAN DALAM MEDIA ONLINE JERMAN: KAJIAN ANALISIS WACANA KRITIS - Shany Pebrianti, - (2020)
This study examines the representation of women victims of sexual harassment in Tagesspiegel's online media by answering research questions on how the Tagesspiegel's reports sexual harassment against German women perpetrated by German men and non German men and what the meanings of the two text comparisons mean. This study uses Transitivity analysis and theme-rheme analysis. This study found three results. First, sexual harassment against women by German men perpetrators is described in Tagesspiegel is biased against women. Second, Tagesspiegel's has a discriminatory tendency towards immigrants. Third, the meaning of the comparison of the two types of texts proves the imbalance between the news texts on sexual harassment against women committed by German men and non German men. Keywords: Representation, Critical Discourse Analysis, Transitivity, Sexual Harassment, German Online Media.